Comparative Study on Grouting Protection Schemes for Shield Tunneling to Adjacent Viaduct Piles. (11th August 2021) - Huang, Kan; Sun, Yiwei; He, Jun; Huang, Xianqiang; Jiang, Meng; Li, Yujian
Abstract : Shield tunnels will inevitably pass through viaduct piles at a close distance due to the extensive construction of subways and viaducts in the city. In order to understand the influence of shield tunneling on the deformation of existing pile foundation and grouting protection measures, based on an engineering case, Changsha Metro Line 5 (from South Gaoqiao station to Guitang station), a three-dimensional finite element model was established to analyze the deformation of bridge pile using grouting protection wall with different depths and shapes when the shield tunnel is under construction. The analytical results indicate that the grouting protection wall can effectively reduce the pile displacement; especially the grouting depth is 3 m below the bottom of the tunnel. Moreover, the L-shaped grouting protection wall can effectively reduce the longitudinal displacement of the piles. The present findings may provide a reference for the design and construction of shield tunnels passing through viaduct piles.